2022
DOI: 10.1002/jor.25294
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between knee anatomy and joint laxity using principal component analysis

Abstract: Knee articular geometry and surface morphology greatly affect knee joint mechanics. Intra‐subject variations in bone morphology and the passive range of motion have been well documented in the literature; however, the relationship between these two characteristics is not well understood. The objective of this study was to describe the correlation between knee joint anatomical features and passive range of motion using a statistical model. A principal component model was developed using femoral and tibial artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
4
10
0
Order By: Relevance
“…13,14,16 Therefore, it appears that a flatter, extended tibia plateau allows for more rotation in the transverse plane before the femur reaches the edge of the plateau, while increases in femoral and intercondylar width allow for more rotation of the joint before engaging the soft tissue, as previously proposed. 14 Decreased tibial spines eminences heights further reduces the constraint on the joint to rotate internally and externally during motion.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…13,14,16 Therefore, it appears that a flatter, extended tibia plateau allows for more rotation in the transverse plane before the femur reaches the edge of the plateau, while increases in femoral and intercondylar width allow for more rotation of the joint before engaging the soft tissue, as previously proposed. 14 Decreased tibial spines eminences heights further reduces the constraint on the joint to rotate internally and externally during motion.…”
Section: Discussionsupporting
confidence: 59%
“…Previous PCA-based analyses have similarly found overall size change to be a dominant mode of geometric variation in the tibiofemoral joint. [12][13][14]16,18 However, neither study found a correlation between knee size and abduction-adduction motion. Lynch et al 16 and Shalhoub et al 14 found no correlations between the modes of variation characterized by scaling of the geometry and motion, with no relationship found between size and the internal-external and abduction-adduction laxity envelope or kinematics during deep knee flexion.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They form the patellofemoral joint when they come together the knee is the biggest joint in the human body and is often considered the most strained joint. 1 The arrangement of bones inside the joint serves as a fulcrum for the muscles that flex and extend the knee. The extracapsular, intracapsular, and ligament designs, as well as the cross-joint muscle extensions, provide the joint with the essential stability to withstand the significant biomechanical force exerted on it.…”
Section: Introductionmentioning
confidence: 99%